2022
DOI: 10.3389/fphys.2022.923945
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Transport Modeling: The Key Link Between Lung Infections of Individuals and Populations

Abstract: The recent COVID-19 pandemic has propelled the field of aerosol science to the forefront, particularly the central role of virus-laden respiratory droplets and aerosols. The pandemic has also highlighted the critical need, and value for, an information bridge between epidemiological models (that inform policymakers to develop public health responses) and within-host models (that inform the public and health care providers how individuals develop respiratory infections). Here, we review existing data and models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…Furthermore, we also observed a significant size growth and tighter size distribution of the emitted particles as the device ages, which agrees with the measurements from a previous study that observed high particle concentration and submicron-sized particles in the ENDS-emitted aerosol [ 41 , 42 ]. In particular, increasing particle sizes with a narrower particle size distribution can enhance respiratory deposition and sedimentation rate of hazardous particle components within the ENDS aerosol [ 43 , 44 , 45 ]. For instance, our inhalation dosimetry analysis showed a significant increase in particle mass deposition and deposited surface area as the device ages, which is shown to be highly affected by changes in particle sizes and concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we also observed a significant size growth and tighter size distribution of the emitted particles as the device ages, which agrees with the measurements from a previous study that observed high particle concentration and submicron-sized particles in the ENDS-emitted aerosol [ 41 , 42 ]. In particular, increasing particle sizes with a narrower particle size distribution can enhance respiratory deposition and sedimentation rate of hazardous particle components within the ENDS aerosol [ 43 , 44 , 45 ]. For instance, our inhalation dosimetry analysis showed a significant increase in particle mass deposition and deposited surface area as the device ages, which is shown to be highly affected by changes in particle sizes and concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Another plausible mechanism is through inhalation of infected droplets as considered in the present study. Residual inhaled droplets or those formed by aerosolisation of the infected mucosa (due to interaction of the infected mucosa with airflow) are subsequently transported from the nasopharynx deeper into the lung where they can release the viruses causing further infection ( Darquenne et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is through inhalation of infected droplets, present in the nasopharynx, deeper into the LRT. These may be the droplets inhaled from the enivronment (which have not deposited in the URT), or those formed due to aerosolization of infected nasopharyngeal mucosa (ANM) ( Edwards et al., 2021 ; Darquenne et al., 2022 ). Hydrodynamic interaction between breathed air and the infected nasopharyngeal mucosa may cause the latter to aerosolize in certain conditions creating virus-laden aerosols/droplets ( Moriarty and Grotberg, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…The intricate geometry of the extra-thoracic that includes bends, expansions and constrictions leads to transition to turbulent airflows in the pharynx, larynx and trachea with Reynolds numbers on the order of several thousands (i.e., 2'000-10'000), depending on inhalation regimes [1][2][3][4]. Detailed modeling of these complex flows is required to determine the fate of particle-laden airflows and ensuing deposition patterns towards predicting for example pulmonary dosimetry [5] or the dispersion of airborne pathogen in the lungs [6,7].…”
Section: Introductionmentioning
confidence: 99%